Salts or complexes? Factors affecting the type of binding of biogenic organic amines by carboxyl derivatives of 1, 1′-dinaphthylmethanes and calix[4]resorcinarenes. (16th July 2022) - Serkova, Olga S.; Glushko, Valentina V.; Toropygin, Ilya Yu.; Maslennikova, Vera I.
Abstract: Polycyclic carboxyl-containing compounds were synthesized by alkaline hydrolysis of 1, 1′-dinaphthylmethane and rctt ortho -methyl-tetra- С -naphthyl-calix[4]resorcinarene esters. Reactions of the obtained products with biologically active amines (ethanolamine, benzylamine, phenethylamine, tyramine, tryptamine) resulted in series of derivatives. Dinaphthylmethane acids formed ammonium salts with all of the used amines; in the case of resorcinarene acids, the outcome of the reaction depended on the combination of reactants: either salts or supramolecular systems were obtained. Irrespective of the structure of molecular platform, all ethanolamine salts and some dinaphthylmethane and resorcinarene salts of benzylamine, phenethylamine, and tyramine were readily soluble in water. Graphical abstract: Image 1